Manual of Maintenance: 1 Buildings and Building Services - Clements, R.; Parkes, D. (London : Business Publications Limited, 1965)
This is a handbook examines building maintenance and management which cover: the function of maintenance; control of plant engineering Department; management techniques; plant replacement; capital work and staff training.
Includes index.
lje 22/01/19
Loans
Keywords: Buildings--Repair and reconstruction; Buildings--Maintenance; Maintenance